CHOP and R-CHOP Therapeutic Responses in Non-Hodgkin Lymphoma Patients in Dr. Soetomo General Hospital Surabaya - Rina Syarifah Salma; Made Putra Sedana; S. Ugroseno Yudho (Faculty of Medicine, Universitas Airlangga, Surabaya, Indonesia, 2018)
Introduction: Non-Hodgkin Lymphoma (NHL) is a group of lymphoid-derived malignant disease with heterogenic biological and clinical manifestations. For over 30 years, CHOP (Cyclophosphamide, Doxorubicin, Vincristine, and Prednisone) has been the first choice of chemotherapy for aggressive NHL. Later in 1997 Rituximab as anti-CD20 monoclonal antibody was introduced and then combined with CHOP as R-CHOP. The objective of this study is to acknowledge the response of the CHOP and R-CHOP therapy in Non-Hodgkin Lymphoma patients at Dr. Soetomo General Hospital.Methods: The design of this study was retrospective observational study using secondary data obtained from patient’s medical records from 2011 to 2015. The data selected from the medical records are the result of the therapy, as well as patient’s gender and age. Results: The results of patients’ therapy were classified into four categories: The study showed that 51.28% patients had Complete Response, followed by Partial Response (28.21%), Progressive Disease (17.95%), and No Change (2.56%). Sample characteristics showed male patients in higher percentage (66.67%), and the majority of patients’ age between 51-60 years old (30.77%). The use of CHOP and R-CHOP regiment were 76.92% and 20,52% respectively.Conclusion: Most of the patients had a complete response. The CHOP regiment is more commonly used in patients compared to R-CHOP.